The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.autrev.2006.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Mini-array of multiple tumor-associated antigens to enhance autoantibody detection for immunodiagnosis of hepatocellular carcinoma

Abstract: Liver cancer, especially hepatocellular carcinoma (HCC), is particularly prevalent in Africa and Asia. HCC affects the Hispanic population of the United States at a rate double that of the white population. The majority of people with HCC will die within 1 year of its detection. This high case-fatality rate can in part be attributed to lack of diagnostic methods that allow early detection. How to establish a methodology to identify the high-risk individuals for HCC remains to be investigated. The multifactoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…These results indicated that autoantibodies against 14-3-3ζ in HCC sera might be potential biomarkers for early-stage HCC screening and diagnosis. Our previous studies have demonstrated that the sensitivity using a single anti-TAA antibody as biomarker in HCC diagnosis is usually not very high, and using a mini-array of multiple TAAs to enhance anti-TAA antibody detection may be an optimal approach in HCC immunodiagnosis [3234]. In the current study, although the detection of anti-14-3-3ζ antibody itself in HCC does not have enough sensitivity for HCC diagnosis, it can still be used as an optimal TAA adding to the panel of TAAs we have selected and validated in our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that autoantibodies against 14-3-3ζ in HCC sera might be potential biomarkers for early-stage HCC screening and diagnosis. Our previous studies have demonstrated that the sensitivity using a single anti-TAA antibody as biomarker in HCC diagnosis is usually not very high, and using a mini-array of multiple TAAs to enhance anti-TAA antibody detection may be an optimal approach in HCC immunodiagnosis [3234]. In the current study, although the detection of anti-14-3-3ζ antibody itself in HCC does not have enough sensitivity for HCC diagnosis, it can still be used as an optimal TAA adding to the panel of TAAs we have selected and validated in our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on this, three categories of tissue microarray can be defined:4 (1) With multitumor arrays, many tumor types are sampled, from a diverse set of donor blocks, and arrayed on one recipient tissue microarray block. With this type of tissue microarray, a large group of tumors can then be expeditiously screened for the presence or absence of novel markers 2830. (2) For tumor progression arrays, morphological and molecular changes through the different stages of tumor progression, of one particular tumor type, can be assessed in tumor progression tissue microarrays.…”
Section: Tissue Microarray Techniquementioning
confidence: 99%
“…Tumour resection is currently the best treatment choice among the numerous therapy methods available. However, HCC is often diagnosed at a late stage, when the prognosis is poor, and many patients die within 1 year after the detection of HCC . Therefore, the identification of effective markers to predict the outcome of HCC patients accurately is necessary.…”
Section: Introductionmentioning
confidence: 99%